The Effect Of Health Education In Pregnant Mothers Against Knowledge About Preeklampsia - Haerani; Andi Suswani; Miftahul Jannah (Jurnal Life Birth, 2020)
Preeclampsia is a collection of symptoms that arise in pregnant women consisting of hypertension, edema, and urinary protein symptoms usually appear after 28 weeks of pregnancy or more. The maternal mortality rate in Indonesia is still high at 305 per 100,000 live births, seen from the health status of the mother, especially pregnant women, 28.8% of pregnant women suffer from preeclampsia. The high rate of maternal and infant mortality in Indonesia cannot be separated from various influencing factors including the lack of health awareness. Lack of maternal knowledge of the incidence of preeclampsia in pregnant women is the cause of the increased number of preeclampsia, therefore it is necessary to provide health education so that mothers can know the signs and symptoms of preeclampsia and complications that will occur. Herlang Health Center Herlang District. The research design used in this study is Pre Experimental Design with the One-Group Pretest-Posttest Design approach. The population in this study as many as 93 people in the Herlang Health Center Herlang District with many respondents 45 pregnant women. The sampling technique is Non-probability sampling. Statistical test using the Wilcoxon test. Results: In the knowledge of the mother obtained a value of P = 0,000 (p <0.05), it was concluded that there were significant differences in knowledge between before being given health education and after being given health education to pregnant women. Conclusion: There are differences in proportions before and after health education is given. Suggestion: Health education is given regularly to prevent preeclampsia.